Novel TMEM173 Mutation and the Role of Disease Modifying Alleles - Keskitalo, Salla; Haapaniemi, Emma; Einarsdottir, Elisabet; Rajamäki, Kristiina; Heikkilä, Hannele; Ilander, Mette; Pöyhönen, Minna; Morgunova, Ekaterina; Hokynar, Kati; Lagström, Sonja; Kivirikko, Sirpa; Mustjoki, Satu; et al. (Frontiers in Immunology, 2019)
Upon binding to pathogen or self-derived cytosolic nucleic acids cyclic GMP-AMP synthase (cGAS) triggers the production of cGAMP that further activates transmembrane protein STING. Upon activation STING translocates from ER via Golgi to vesicles. Monogenic STING gain-of-function mutations cause early-onset type I interferonopathy, with disease presentation ranging from fatal vasculopathy to mild chilblain lupus. Molecular mechanisms underlying the variable phenotype-genotype correlation are presently unclear. Here we report a novel gain-of-function G207E STING mutation causing a distinct phenotype with alopecia, photosensitivity, thyroid dysfunction, and features of STING-associated vasculopathy with onset in infancy (SAVI), such as livedo reticularis, skin vasculitis, nasal septum perforation, facial erythema, and bacterial infections. Polymorphism in TMEM173 and IFIH1 showed variable penetrance in the affected family, implying contribution to varying phenotype spectrum. The G207E mutation constitutively activates inflammation-related pathways in vitro, and causes aberrant interferon signature and inflammasome activation in patient PBMCs. Treatment with Janus kinase 1 and 2 (JAK1/2) inhibitor baricitinib was beneficiary for a vasculitic ulcer, induced hair regrowth and improved overall wellbeing in one patient. Protein-protein interactions propose impaired cellular trafficking of G207E mutant. These findings reveal the molecular landscape of STING and propose common polymorphisms in TMEM173 and IFIH1 as likely modifiers of the phenotype.